1999
DOI: 10.1159/000016937
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Bowel Disease and Pregnancy: A Review

Abstract: Inflammatory bowel disease often occurs during peak reproductive years. Rates of conception, pregnancy outcome and disease course during pregnancy should be discussed prior to attempted conception. The majority of patients whose disease is well controlled prior to pregnancy should expect a fertility rate comparable to the general population, and an uncomplicated pregnancy with a favorable outcome. The disease should continue to be pharmacologically or surgically controlled as necesssary during pregnancy; the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…We confirmed that disease activity prior to conception correlates with disease activity during pregnancy [ 2 , 3 , 12 , 13 ]. Antenatal disease activity did not increase the risk of emergency CS, suggesting that disease activity alone should not be classed as an indication for elective CS in IBD patients.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…We confirmed that disease activity prior to conception correlates with disease activity during pregnancy [ 2 , 3 , 12 , 13 ]. Antenatal disease activity did not increase the risk of emergency CS, suggesting that disease activity alone should not be classed as an indication for elective CS in IBD patients.…”
Section: Discussionsupporting
confidence: 72%
“…As disease activity at conception often predicts disease activity during pregnancy, patients with IBD should aim for remission prior to pregnancy [ 2 , 3 , 4 , 5 , 6 ]. In patients with active disease, the risk of adverse maternal and neonatal outcomes increases; thus, careful monitoring, medication optimisation, and input from gastroenterologists are essential for the obstetric care of patients with IBD [ 2 , 3 , 4 , 5 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations